2018
DOI: 10.1089/crispr.2018.0040
|View full text |Cite
|
Sign up to set email alerts
|

Is Enhancement the Price of Prevention in Human Gene Editing?

Abstract: New gene-editing tools challenge conventional policy proscriptions of research aimed at either human germline gene editing or human enhancement by potentially lowering technical barriers to both kinds of intervention. Some recent gene-editing reports have begun to take up the prospect of germline editing, but most experts are in broad agreement that research should prioritize medical applications over attempts to enhance human traits. However, there is little consensus about what counts as human enhancement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Framing scientific progress within a novel human rights-based approach would ‘reorient our conversation from policing science to governing society and would shift our focus from avoiding risks to protecting opportunities’ (p. 21) 66. Indeed, this would foster advancements in our ability to treat and prevent disease, while remaining mindful of the need to establish anticipatory governance that provides the necessary flexibility to frame the preventive or therapeutic applications but also adapt to potentially legitimate ‘off-label’ ones 67. Finally, addressing the notion of ‘serious’ could also profit from future discussion of another human right, that of ‘future generations’, iv as the need for intergenerational monitoring will undoubtedly lead to safety, privacy, and consent issues for children not yet born 51…”
Section: Resultsmentioning
confidence: 99%
“…Framing scientific progress within a novel human rights-based approach would ‘reorient our conversation from policing science to governing society and would shift our focus from avoiding risks to protecting opportunities’ (p. 21) 66. Indeed, this would foster advancements in our ability to treat and prevent disease, while remaining mindful of the need to establish anticipatory governance that provides the necessary flexibility to frame the preventive or therapeutic applications but also adapt to potentially legitimate ‘off-label’ ones 67. Finally, addressing the notion of ‘serious’ could also profit from future discussion of another human right, that of ‘future generations’, iv as the need for intergenerational monitoring will undoubtedly lead to safety, privacy, and consent issues for children not yet born 51…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, embryo editing in clinical treatments could accidentally cause human enhancement in several ways. For example, it has been shown that the overexpression of genes to prevent neurological diseases can improve the cognitive potential of mouses and even increase the life span by up to 30% (40). Before starting to write the political outlines, this type of pleiotropic effects must be considered from all spheres of society.…”
Section: Abraham Lincolnmentioning
confidence: 99%
“…Though current translational projects are mostly focused on prevention of monogenic disorders, there are other potential applications of GGE that have received some attention. The most prominent is the use of GGE to lower risk of communicable or non-communicable disease, such as editing to confer limited or full immunity to common pathogens or to lower risk of chronic conditions such as heart disease [ 66 – 68 ]. The experiments conducted by He Jiankui were of this type—as discussed in the “ Introduction ” section, He was attempting to disable the CCR5 gene and so confer some immunity to HIV infection.…”
Section: What Is the Potential Clinical Utility Of Germline Gene Editmentioning
confidence: 99%